The abundance of sterile transcripts in Giardia lamblia - Elmendorf, Heidi G. (Oxford University Press, 2001)
The protozoan parasite Giardia lamblia synthesizes a diverse and surprisingly abundant array of sterile transcripts unable to code for proteins. Random sampling of cDNAs from two evolutionarily divergent Giardia strains indicates that ∼20% of cDNAs in the libraries represent polyadenylated sterile transcripts. RNase protection analysis and northern blot hybridization of three sterile transcript loci demonstrated that both the sterile transcript and a complementary mRNA were made in each case, further categorizing these sterile transcripts as antisense transcripts. Investigation of the genomic loci for these same three sterile antisense transcripts showed typical transcription units for the sense transcripts, but still failed to reveal a usable open reading frame for the sterile antisense transcripts. 5′-RACE mapped the transcription start site for one of the sterile antisense transcripts to an AT-rich region, as is typical for Giardia. It is unclear whether these sterile transcripts represent errors in transcription or whether they have regulatory functions within the cell, although preliminary investigations failed to reveal evidence for a role in developmental gene regulation. In either case, the presence of such a large pool of sterile antisense transcripts is dramatic evidence of the unusual molecular machinery of the early diverging protist G.lamblia.